Peptide-Mediated Immobilization on Magnetoferritin for Enzyme Recycling - Zhang, Yu (Nanomaterials (Basel), 2019)
Ferritin possess favorable properties because its exterior and interior surface can be applied to generate functional nanomaterials, which make them possible for enzyme immobilization and recycling. Here, we report the noncovalent immobilization of a genetically modified β-glucosidase onto the outer surface of synthetic magnetoferritin through the electrostatic interaction of a heterodimeric coiled-coil protein formed by coils containing lysine residues (K-coils) and coils containing glutamic acid (E-coils). The immobilized enzyme was characterized, and its enzymatic properties were evaluated. Furthermore, reusability of immobilized enzyme was demonstrated in aqueous solution under an applied magnetic field. The results showed that magnetoferritin was successfully prepared and it was an excellent support for enzyme immobilization. After three times usages, the retention rates were 93.75%, 82.5%, and 56.25%, respectively, demonstrating that immobilized enzyme possessed good retention efficiency and could be used as potential carrier for other biomolecules. The strategy of enzyme immobilization developed in this work can be applied, in general, to many other target molecules.